Kewenangan Pemerintah Daerah Khusus Ibu Kota Jakarta Dalam Menangani Sampah Medis Saat Pandemi Covid-19: Authority of the Special Capital City Regional Government of Jakarta in Handling Medical Waste During the COVID-19 Pandemic - Bryan Akmal; Wiratno (Faculty of Law, Universitas Trisakti, 2024)
This article elaborates on the Government's authority in handling medical waste during the COVID-19 pandemic. The writing of this article is dine the normative juridical research method by taking data sources from primary data and secondary data. Data analysis is carried out qualitatively, and conclusions using deductive logic. Law number 32 of 2009 concerning Environmental protection and Management becomes the lrgal basis in regulating waste management, especially medical waste. This article research that examines main problem is, focus on the policy of the DKI Jakarta regional Government in handling health waste during the COVID-19 pandemic period and then explore the supporting and inhibiting factors that affect the management of medical waste by the DKI Jakarta Regional Government in the region. The results of the discussion of his article are expected to provide input for the improvement of policies and actions in improving the affectiveness of medical waste handling during the pandemic and other emergency health situations. The conclusion the discussion and the conclusions of this article show that Circular Letter No.SE.2/MENLHK/PSLB3/PLB.3/3/2020 regulates the management of infectious medical waste during COVID-29 in Jakarta. DKI Jakarta is experiencing regulatory constraints, processing capacity, institutional coordination, human resources, and financing.